Molecular responses of U87-glioblastoma multiform cancer stem cells to HSV-G47Δ oncolytic virus in normoxia and hypoxia tumor microenvironments - Reza, Vazifehmand Rodposhtei (2021)
Among young adults, Glioblastoma (GBM, WHO IV astrocytoma) is the most common and aggressive form of primary brain tumor and it is highly invasive with the potential to spread to the central nervous system. Despite the current standard therapies, which include surgery, chemotherapy and radiation, it is still considered a deadly disease. The mean survival rate of glioblastoma patients is 12-14 months. The GBM cancer stem cell subpopulation within tumor processes play a critical role in tumor initiation, progression, and local recurrence and which are resistant to standard therapies. Different genetic pathways such as PI3K/AKT, RTK/RAS, p53, RB, PKR, Apoptosis, telomerase, telomere length alterations, autophagy, mitophagy, angiogenesis and multiple functional of noncoding RNAs including microRNAs and Lung non coding RNAs are involved in GBM progression and its invasion. Resistance to chemotherapy treatment can occur in low tumor oxygenation environment (hypoxia). As a novel therapeutic strategy for GBM treatment, live and engineered oncolytic viruses such as HSVG47 delta (a 3rd generation of HSV-1 with ICP6-, ˠ 34.5-, α47-, lac Z+) with limited toxicity are applied, and they can specifically target apoptosis-resistance cancer stem cells without cross-resistance with existing therapies; hence, the normal cells are spared. Although the HSV-G47Δ oncolytic virus has been applied to treat different kinds of solid tumors such as glioblastoma, its molecular targets in U87-GBM CSCs were in a Curtain of ambiguity. Therefore, PI3K/AKT, RTK/RAS, p53, RB, PKR, Apoptosis, telomerase, telomere length alterations, autophagy, mitophagy, angiogenesis, and non-coding RNAs were the main objective pathways that were evaluated by HSV-G47Δ oncolytic virus in normoxia and hypoxia tumor microenvironments. To achieve this purpose, First, GBM-CSCs neurospheres were isolated in DMEM/F12 serum free media and characterized using monoclonal antibodies (CD133-PE, CD44-FITC and DAPI staining) by immunocytochemistry method. Flow cytometry was conducted for apoptosis and cell cycle distribution. Cell viability assay and CPE effects were performed using a standard protocol. Different genetic pathways (mentioned above) were evaluated at the level of mRNA expression in normoxia and hypoxia niches exposed to HSV-G47Δ oncolytic virus using a custom RT2Profiler™ PCR Array and Q-PCR methods. In-silico pathway analysis was performed using online bioinformatics tool (GENE-MANIA) to detect physical and genetic interactions between dysregulated genes. Findings showed that GBM-CSCs could be specifically targeted by HSV-G47Δ oncolytic virus in both microenvironments and the cells were arrested at early stage of apoptosis and G0/G1 cell cycle. Furthermore, results indicated that HSV-G47Δ is more effective when the glioblastoma cancer stem cells are in hypoxic condition. Out of 169 evaluated genes of different pathways, 51genes were significantly in dysregulated pattern when GBM-CSCs exposed to HSV-G47Δ. One of the impressive results of the study was the effects of HSV-G47Δ virus on telomere length alterations with had increased under normoxic condition while a significant telomere shortening was observed when the U87-CSCs were exposed to HSV-G47Δ virus in hypoxic. Data showed that out of forty three miRNAs, eight miRNAs including miR-7-1, miR-let-7b, miR-130a, miR-137, miR-200b, miR-221, miR-222 and miR-874 were significantly over expressed in normoxic microenvironment. Expression level of LncRNAs including LEF1-AS1, MALAT1, LINC00470, TUSC7, HOTAIR, NEAT1 and XIST were significantly down regulated in hypoxic microenvironment and H19 did not have any dysregulated pattern in this niche. In normoxic condition, LEF1-AS1, MALAT1, LINC00470, H19, HOTAIR, NEAT1 and XIST were under regulated and TUSC7 was not targeted by HSV-G47Δ. Furthermore, in hypoxic conditions, PERK, ING-G, LC3, MFN2, PINK-1, and PARKIN were significantly downregulated while INF-G, P62, LC3, and PARKIN were in the upregulated pattern. The findings revealed that high-grade glioblastoma cancer stem cells were potentially controlled by HSV-G47Δ oncolytic virus in both autophagy and mitophagy pathways at hypoxic conditions. Our results also showed the expression of the majority of genes in MDR pathway (Exception DKC1down regulated) were significantly up in GBM-CSCs when the cells were inoculated with HSV-G47Δ (MOI=1,14h) in normoxic condition while most genes were down regulated under HSV-G47Δ (MOI=1,14h) in hypoxic condition. Pathway analysis showed genetic and physical interactions among dysregulated genes in both microenvironments in the most biological pathways. In conclusion, HSV-G47Δ has a therapeutic potential to control crucial mechanisms in GBM-CSCs progression and could be considered as a promising strategy in GBM treatment, especially when the cells have a high grade of tumorigenicity in hypoxic niche.